Mahua flowers (Madhuca sp.) utilization as a carbon-rich natural substrate for the cost-effective bench-scale production of fumaric acid - Singh K.; Sharma D.; Mishra A. (My University, 2025)
Fumaric acid is a multi-functional bio-based organic acid that is extensively used as a building block compound in chemical synthesis, food preservative and as therapeutics. The substrates required for the production are the sugars that account for 50–60% of the total process economics. The present work explores the utilization of Mahua flowers as a cheaper carbon source and low cost production medium for cost-effective fumaric acid production using Rhizopus oryzae. Various process parameters for fumaric acid production and desired fungal morphology were investigated, including Mahua flower extract concentration, fermentation temperature, fermentation pH and agitation speed. The highest concentration of the product, fumaric acid obtained in shake flask was 23.5 ± 0.9 g/L at optimized conditions of 100 g/L of Mahua flower extract medium, pH 6, 30 ℃ temperature and shaking speed of 200 rpm in 72 h. The pellet morphology resulted in higher production than mycelial clumps. Bench-scale production in stirred tank reactor resulted in 24.1 ± 1.0 g/L of fumaric acid production at an aeration rate of 1 vvm, agitation at 200 rpm and temperature of 30 ℃. The results obtained were comparable to fermentation with pure glucose. The present study evidently reveals the feasibility of carbon-rich, low cost, abundantly available natural substrate for cost-effective fumaric acid production. © 2021, The Author(s).